Spatial distribution correlation of soil-gas radon (222Rn) and mercury with leveling deformation in northern margin fault zone of West Qinling, China. (November 2017) - Li, Chenhua; Zhang, Hui; Su, Hejun; Zhou, Huiling; Wang, Yanhong
Abstract: This study concerns measurement of 222 Rn and mercury concentrations in soil-gas in the northern margin fault zone of West Qinling, Tibet (China). Based on profiles crossing perpendicularly the different segments of the fault at six different locations, the relations between the gas measurements, fault deformation, and seismic activity in each segment of the studied fault were analyzed, determining seismic risks in the fault zone. Soil-gas data are heterogeneous, but appear relatively organized along the three segments of the fault. The detailed multidisciplinary analysis reveals complex interactions between the structural setting, uprising fluids, leveling and seismic activity in different fault segments. The results for both fault soil gas and deformation indicated relatively stronger fault activity in the Wushan segment in the middle-eastern segment of the northern margin fault zone of West Qinling and lower activity in the Zhangxian segment, whereas the fault in the Tianshui segment was relatively locked. Additionally, in the Wushan strike-slip pull-apart area, the active influence of fluid activities facilitated the occurrence of small to medium-sized seismic events, which prevented the occurrence of larger events; in contrast, in the Tianshui segment, the west Zhangxian segment, the weak fluid activities and the corresponding strain rate will probably lead to strong earthquake buildup. Highlights: The concentration characteristics of 222 Rn and Hg emissions are synchronously measured. Soil-gas data were compared with seismic activity and leveling deformation characteristics. The relationship could help discriminate between locked and unlocked segments of the fault.